2021
DOI: 10.1186/s12935-021-01911-1
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MONC suppresses the malignant phenotype of Endometrial Cancer Stem Cells and Endometrial Carcinoma Cells by regulating the MiR-636/GLCE axis

Abstract: Background Emerging evidence shows that abnormal expression of long non-coding RNA is involved in the occurrence and development of various tumors. LncRNA MONC is abnormally expressed in head and neck squamous cell carcinoma, lung cancer, colorectal cancer, and acute megakaryocytic leukemia, but the biological function and potential regulatory mechanism of MONC in endometrial cancer stem cells (ECSCs) and endometrial cancer cells (ECCs) have not been studied. In this study, we aimed to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Recently, increasing evidence indicated that lnc-RNAs were implicated in the formation and development of EC. For example, Li et al [ 15 ] demonstrated that lnc-MONC restrains the grade malignancy of endometrial cancer stem cells (ECSCs) and endometrial cancer cells (ECCs) by ordering the miR-636/GLCE axis. Similarly, lncRNA HOXB-AS3 was upregulated in endometrial cancer tissues and cell lines, enhanced cell proliferation, and inhibited apoptosis in EC cells [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing evidence indicated that lnc-RNAs were implicated in the formation and development of EC. For example, Li et al [ 15 ] demonstrated that lnc-MONC restrains the grade malignancy of endometrial cancer stem cells (ECSCs) and endometrial cancer cells (ECCs) by ordering the miR-636/GLCE axis. Similarly, lncRNA HOXB-AS3 was upregulated in endometrial cancer tissues and cell lines, enhanced cell proliferation, and inhibited apoptosis in EC cells [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…We and others have revealed that MIR99AHG can act as an oncogene in myeloid leukaemia and gastric cancer 45,46 . Nevertheless, it was also reported as a tumor suppressor in lung adenocarcinoma and endometrial carcinoma 47,48 , highlighting the functional complexity and tumor specificity of MIR99AHG. In the present study, we found that MIR99AHG is upregulated in CRC cell lines, especially in those with a high metastatic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Another example is bta-miR-26a which also reduced the abundance of PCK1 [44,45]. Moreover, the oncosuppressor miR-20a-3p was identified in melanoma, tongue squamous cell carcinoma, and hepatocellular carcinoma, and the oncosuppressor miR-636 was also identified in lung cancer, nasopharyngeal carcinoma, cervical cancer, endometrial cancer, ovarian cancer, and hepatocellular carcinoma [46][47][48][49][50][51][52][53][54][55][56]. It was reported that high miR-20a-3p and miR-636 expression were correlated with poor OS of CRC patients and this was consistent with our results.…”
Section: Discussionmentioning
confidence: 99%